A crippled city? The image of Königsberg/Kaliningrad in Polish literature and journalism (selected examples) - Bobryk, Roman (Porównania, 2024)
The contemporary perception of Königsberg is largely influenced by its twentieth century history. The city’s historic buildings were almost completely destroyed as a result of the British bombing in August 1944. After the war, the city was incorporated into the Soviet Union which was not interested in rebuilding culturally foreign monuments. Therefore, not only were the former German buildings not renovated, but also the traces of German heritage were removed: in 1968, the ruins of the royal castle were demolished, and near the place where it stood, the construction of the enormous House of Soviets began. Contemporary Königsberg, however, is more frequently returning to its own history - which has been rejected for years - to try to build its own identity upon it. This balancing between the post-Soviet present and the Germanic (including Nazi) past appears in both contemporary Polish literature and journalism about the capital of this Russian exclave.